Prophylactic thyroidectomy in children with multiple endocrine neoplasia type 2. Issue 10 (17th April 2018) - Prete, F. P.; Abdel‐Aziz, T.; Morkane, C.; Brain, C.; Kurzawinski, T. R.; ,
Abstract : Background: In patients with multiple endocrine neoplasia type 2 (MEN2) syndrome, genetic testing offers early diagnosis, stratifies the risk of developing medullary thyroid cancer (MTC) and informs the timing of thyroidectomy. The efficacy of treatment, which depends on timely and safe surgery, is not well established. Methods: This was a retrospective review of diagnostic and clinicopathological outcomes of prophylactic thyroidectomy in children with MEN2 between 1995 and 2013 in the UK. American Thyroid Association (ATA) 2009 guidelines were used as a benchmark for adequate treatment. Results: Seventy‐nine children from 16 centres underwent total thyroidectomy. Thirty‐eight patients (48 per cent) underwent genetic testing and 36 (46 per cent) had an operation performed above the age recommended by the ATA 2009 guidelines; pathology showed MTC in 30 patients (38 per cent). Late surgery, above‐normal preoperative calcitonin level and MTC on pathology correlated with late genetic testing. Twenty‐five children had lymphadenectomy; these patients had more parathyroid glands excised (mean difference 0·61, 95 per cent c.i. 0·24 to 0·98; P = 0·001), and were more likely to have hypocalcaemia requiring medication (relative risk (RR) 3·12, 95 per cent c.i. 1·54 to 6·32; P = 0·002) and permanent hypoparathyroidism (RR 3·24, 1·29 to 8·11; P = 0·010) compared with those who underwent total thyroidectomy alone. Age did not influence the development of complications. Conclusion: Late genetic testing may preclude age‐appropriate surgery, increasing the risk of operating when MTC has already developed. Early genetic testing and age‐appropriate surgery may help avoid unnecessary lymphadenectomy and improve outcomes. Abstract : Centralization needed